Dialogue-Based Learning: A Framework for Inclusive Science Education and Applied Ethics - Romano, Michael R.; Díaz-Almeyda, Erika; Namdul, Tenzin; Lhundup, Yeshi (Frontiers in Communication, 2021)
Dialogue-based learning is an inclusive pedagogy that leverages epistemological pluralism in the classroom to enhance cross-cultural education, encourage critical thinking across modes of inquiry, and promote novel contributions in applied ethics. The framework emerged from the Buddhism-science dialogue and our experiences teaching science courses for Tibetan Buddhists in India through the Emory-Tibet Science Initiative. Buddhism and science are two modes of inquiry that emphasize critical inquiry and empiricism, yet navigating complementarities and points of friction is challenging. Our proposed framework aims to raise awareness of onto-epistemological assumptions to convert them from obstacles into assets in dialogue. In drawing attention to epistemological orientations, our framework demonstrates that receptivity to other ways of knowing fosters clarity in one’s own views while creating space for new and enriching perspectives. In this article, we contextualize the Buddhism-science dialogue, explore the development of our dialogue-based learning framework, and demonstrate its application to a novel exchange about the COVID-19 pandemic. Broader aims of the framework include increasing scientific literacy and advancing transdisciplinary research.